The evolution of Halls of Fame in graffiti writing and my run to a masterpiece - Hilmer, Christopher D (Street Art & Urban Creativity, 2018)
Cultural and urban geographical research related to graffiti and street art poses interdisciplinary questions and employs multi-methodical approaches. In recent years, research methods in the field of ethnography have been receiving more and more attention in the German-speaking community of human geography. With this in mind, the following working paper presents a methodological experiment for examining the everyday urban practice of graffiti writing and its spatial relevance. “My run to a masterpiece” presents the current status of this ethnographic research, whereby it has been attempted to localize and analyze legal walls for graffiti writing (some of them considered “Halls of Fame”) in the urban cultural landscape as well as these walls’ potential for integrated urban development policies in Germany.